2023
DOI: 10.3390/metabo13121201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Garlic Straw with Silage Corn Stalks on Hu Sheep Rumen Fermentation and Microbial Community In Vitro

Yangyang Shen,
Jianli Zhang,
Hongbing Gui
et al.

Abstract: Garlic, an important economic crop, provides nutrient-rich straw. When appropriately balanced with silage corn stalks, it is a high-quality forage resource. However, studies on the impact of garlic straw with silage corn stalks on Hu sheep’s digestive metabolism and rumen microbiota are scarce. In this study, different addition ratios of garlic straw and silage corn stalks were utilized for in vitro experiments. We designed six experimental groups (CON, G0, G20, G40, G60, G80, and G100) based on varying ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In addition, this experiment found that Succinivibrio plays an important role in the rumen degradation of both GS and AS. Previous studies have shown that Succinivibrio is among the predominant fiber-dissolving bacteria in the rumen, and its relative abundance is positively correlated with the feed efficiency of ruminants [ 61 ]. This is consistent with the results of this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this experiment found that Succinivibrio plays an important role in the rumen degradation of both GS and AS. Previous studies have shown that Succinivibrio is among the predominant fiber-dissolving bacteria in the rumen, and its relative abundance is positively correlated with the feed efficiency of ruminants [ 61 ]. This is consistent with the results of this experiment.…”
Section: Discussionmentioning
confidence: 99%